Inflammatory Mediator Profiles Differ in Sepsis Patients With and Without Bacteremia - Mosevoll, Knut Anders; Skrede, Steinar; Markussen, Dagfinn Lunde; Fanebust, Hans Rune; Flaatten, Hans Kristian; Aßmus, Jörg; Reikvam, Håkon; Bruserud, Øystein (Frontiers in Immunology, 2018)
Systemic levels of cytokines are altered during infection and sepsis. This prospective observational study aimed to investigate whether plasma levels of multiple inflammatory mediators differed between sepsis patients with and those without bacteremia during the initial phase of hospitalization. A total of 80 sepsis patients with proven bacterial infection and no immunosuppression were included in the study. Plasma samples were collected within 24 h of hospitalization, and Luminex® analysis was performed on 35 mediators: 16 cytokines, six growth factors, four adhesion molecules and nine matrix metalloproteases (MMPs)/ tissue inhibitors of metalloproteases (TMPs). Forty-two patients (52.5%) and 38 (47.5%) patients showed positive and negative blood cultures, respectively. There were significant differences in plasma levels of six soluble mediators between the two ‘bacteremia’ and ‘non-bacteremia’ groups, using Mann–Whitney test (p<0.0014): tumor necrosis factor alpha (TNFα), CCL4, E-selectin, vascular cell adhesion molecule-1 (VCAM-1), intracellular adhesion molecule-1 (ICAM-1) and tissue inhibitor of metalloproteinase-1 (TIMP-1). Ten soluble mediators also significantly differed in plasma levels between the two groups, with p-values ranging between 0.05 and 0.0014: interleukin (IL)-1ra, IL-10, CCL2, CCL5, CXCL8, CXCL11, hepatocyte growth factor (HGF), MMP-8, TIMP-2 and TIMP-4. VCAM-1 showed the most robust results using univariate and multivariate logistic regression. Using unsupervised hierarchical clustering, we found that TNFα, CCL4, E-selectin, VCAM-1, ICAM-1 and TIMP-1 could be used to discriminate between patients with and those without bacteremia. Patients with bacteremia were mainly clustered in two separate groups (two upper clusters, 41/42, 98%), with higher levels of the mediators. One (2%) patients with bacteremia was clustered in the lower cluster, which compromised most of the patient without bacteremia (23/38, 61%) (χ2-test, p<0.0001). Our study showed that analysis of the plasma inflammatory mediator profile could represent a potential strategy for early identification of patients with bacteremia.